Penang Hokkien And Peranakan Rhymes : Teaching The Young On The Cultural Traditions, Values, Early Developmental And Music Skills - Ong , Siew Lee (2010)
When one talks of rhymes, nursery rhymes such as Twinkle,Twinkle Little Star or Baa Baa Black Sheep comes to mind. In Penang, Malaysia where people come from different races, religions and cultures, various types of rhymes exist. This thesis focuses on the Hokkien and Peranakan rhymes of Penang which can be categorized as action songs, songs for singing, work songs, lullabies, singing games, call and response songs, chanting rhymes and story telling rhymes.